TECHNICAL ANALYSIS OF HARTMANN’S RETROSIGMOIDECTOMY IN THE EMERGENCY CONTEXT OF COMPLICATED DIVERTICULITIS HINCHEY III AND IV - Cortes, Karol da Conceição Rabello; Carlos Junior, Marcello Laporta; Uliano, José Vitor; Alves, Samuel Andrade Farias; Rodrigues e Souza, José Vitor; Barros, Dimitri Mota; Almeida, João Victor Fabris; de Moura Neto, José Edson; Brasil, Tatiana Lima; Lopes, Anaísa Filmiano Andrade; Cardoso, Leone Romagnoli; Santos, Paula Fernanda de Araújo Lima; et al. (Seven Editora, 2025)
Hartmann’s retrosigmoidectomy is a widely adopted surgical procedure for managing patients with complicated diverticulitis, particularly in Hinchey III and IV stages. These advanced stages are associated with high morbidity and mortality due to purulent or fecal peritonitis, necessitating emergent surgical interventions. This study presents a systematic technical analysis of Hartmann’s procedure in this emergency context, focusing on outcomes such as mortality, morbidity, stoma reversal rates, and long-term complications. A comprehensive search was conducted in PubMed, Embase, Cochrane Library, and Scopus for studies published between 2016 and 2024, using keywords like "Hartmann’s Procedure," "Complicated Diverticulitis," "Hinchey III and IV," and "Emergency Surgery." Of 34 initially identified studies, 10 met the inclusion criteria. Findings reveal that while Hartmann’s procedure remains a vital option for hemodynamically unstable patients, its limitations, such as low stoma reversal rates (43.9%, Facile et al., 2020) and higher long-term complication rates, underscore the need for patient stratification. Comparatively, primary anastomosis demonstrated superior outcomes in selected stable patients, with higher stoma reversal rates (86.9%, Bridoux et al., 2017) and improved quality of life. Advances in laparoscopic approaches have also shown potential in enhancing outcomes for Hartmann’s procedure. Despite its established role, the procedure’s high morbidity and low reversal rates prompt the need for further research into individualized patient selection and innovative surgical techniques. DOI: https://doi.org/10.56238/sevened2024.037-184